Features of Psychotic Symptoms in Methamphetamine Use Disorder Patients and Ketamine Use Disorder Patients: A Cross-Sectional Study - Luo, Tao; Xiao, Meng; Qi, Chang; Wu, Qiuxia; Tang, Jinsong; Liao, Yanhui (Frontiers in Psychiatry, 2022)
Background: Methamphetamine and ketamine are commonly used club drugs. Both of them have been reported to mimic psychotic symptoms of schizophrenia. However, the prevalence and detailed features of psychotic symptoms among methamphetamine use disorder (MUD) and ketamine use disorder (KUD) patients are largely unknown. This study aimed to measure psychotic symptoms among patients with MUD and KUD. Methods: A total sample of 842 patients from voluntary drug rehabilitation centers, including 462 MUD patients and 380 KUD patients, were invited to this study. The Positive and Negative Syndrome Scale (PANSS) was applied to assess psychotic symptoms in these two groups of patients. Results: The prevalence of psychotic symptoms was significantly higher among MUD patients than KUD patients (75.1% vs 50.5%, 95% CI: 3.532 to 11.858, p < 0.001). Compared with KUD patients, MUD patients were more likely to experience positive symptoms (PANSS positive scores: 11.5 ± 6.07 vs 15.1 ± 8.22, P < 0.001) and negative symptoms (PANSS negative scores: 12.4 ± 6.60 vs 14.5 ± 8.63, P < 0.001), but not general symptoms (PANSS general scores: 31.2 ± 13.90 vs 32.2 ± 15.13, P < 0.001). Conclusions: The current study found that more than half of MUD and KUD patients experienced psychotic symptoms, and that patients with MUD are more likely to experience positive and negative symptoms than patients with KUD. The findings provide a new perspective for exploring the neuropathological mechanism of psychotic symptoms of schizophrenia. Keywords: methamphetamine use disorder, ketamine use disorder, psychotic symptoms, positive symptoms, negative symptoms, schizophrenia